Identity, Repression, and the Collapse of Apartheid (The Strategic Review for Southern Africa, 2021)
Scholars emphasize that an influx of resources during the 1980s lowered the costs of collective action and nourished a mass nonviolent anti-apartheid movement that eventually brought down the incumbent regime. Utilising a discourse theoretic approach, this study demonstrates that the 1976 Soweto massacre along with its antecedent organisational campaign waged by the Black Consciousness movement (BCM) were pivotal, yet overlooked historical factors that contributed to the apartheid collapse. While the Soweto massacre led to the detainment of BCM leadership and the death of leader Steve Biko, the event of white police killing black unarmed students in June of 1976 backfired and revealed central antagonisms and contradictions underpinning the apartheid project. Only once political identities were dislocated did the possibility arise for a unified mass opposition movement to form. Alongside weighing economic costs under threat of state repression, this study demonstrates that historical waves of revolutionary mobilisation are also influenced by identity and meanings that get attribute to repressive events by publics.